From Hahn-Banach to monotonicity. (2nd, expanded ed.) - Simons, S. (Springer, 2017)
36. Subclasses of the maximally monotone multifunctions -- 37. First application of Theorem 35.8: type (D) implies type (FP) -- 38. TCLB(E), TCLBN(B) and type (ED) -- 39. Second application of Theorem 35.8: type (ED) implies type (FPV) -- 40. Second applications of Theorem 35.8: type (ED) implies strong -- 41. Strong maximality and coercivity -- 42. Type (ED) implies type (ANA) and type (BR) -- 43. The closure of the range -- 44. The sum problem and the closure of the domain -- 45. The biconjugate of a maximum TCLB(E**) -- 46. Maximally monotone multifunctions with convex graph -- 47. Possibly discontinuous positive linear operators -- 48. Subtler properties of subdifferentials -- 49. Saddle functions and type (ED) -- VII. The sum problem for general Banach spaces -- 50. Introductory comments -- 51. Voisei's theorem -- 52. Sums with normality maps -- 53. A theorem of Verona-Verona.